Penerapan Metode House Of Risk Pada Aktivitas Pengadaan Pt. Waskita Beton Precast, Tbk Plant Prambon - R. A. Luthfi Asia Fergisya; Rr. Rochmoeljati (Jurnal Kendali Teknik dan Sains, 2024)
PT. Waskita Beton Precast, Tbk Plant Prambon is a manufacturing company that produces precast concrete. In carrying out the production process, PT. Waskita Beton Precast, Tbk Plant Prambon requires materials and services from related vendors. The Supply Chain Management Division is responsible for meeting material and service needs. However, in the process it is not uncommon to encounter several risks that can hamper the company's smooth operations. Therefore, this research recommends the House of Risk method as risk management. From the results of this research, it can be seen that there are 21 risk events and 34 risk causes. The results of House of Risk phase 1 are that there are 9 causes of risk that need to be formulated risk mitigation strategies. The results from House of Risk phase 2 obtained 9 risk mitigation strategies